Shared decision-making for postoperative analgesia: A semistructured qualitative study. Issue 1 (January 2019) - van den Berg, Amalia M.A.; Stalmeier, Peep F.M.; Scheffer, Gert Jan; Hermens, Rosella P.; Bucx, Martin J.L.
Abstract : BACKGROUND: Shared decision-making (SDM) and decision-support tools have attracted broad support in healthcare as they improve medical decision-making. Experts disagree on how these can help patients evaluate their present situation and possible outcomes of therapy, and how they might reduce decisional conflict. Little is known about their implementation, especially in anaesthesiology. OBJECTIVE: To obtain a more fundamental understanding of pre-operative SDM and evaluate the use of a decision-support tool for postoperative analgesia after major thoracic and abdominal surgery. DESIGN: A qualitative study with semistructured, in-depth interviews of patients and professionals. SETTING: Patient recruitment took place at the Radboud University Medical Centre in Nijmegen and the Canisius Wilhelmina Hospital in Nijmegen, a nonacademic teaching centre. Professionals of the Radboud University Medical Centre were invited to participate in the interviews. PARTICIPANTS: Interviews were performed with 10 individual patients and two focus groups both consisting of eight different professionals. MAIN OUTCOME MEASURES: To gain insight into the provision of pre-operative information, decision-making processes and the clarity and usability of a prototype decision-support tool. RESULTS: Professionals seemed to provide their patients with information directed towards the application of epidural analgesia, providing little attention to its negative effects. For many patients, the information was not tailored to their needs. Patients' involvement in decision-making was minimal, but they did not feel a need for more involvement. They were positive about the decision-support tool, although they indicated that it would not have influenced their treatment decision. Professionals expressed their doubt about the capacity of their patients to fully understand the decisions involved and about the clinical usability of the decision-support tool, because patients might misinterpret the information provided. CONCLUSION: The results of this study suggest that both patients and professionals did not adhere to some 'self-evident' principles of SDM when postoperative analgesia after major thoracic and abdominal surgery was discussed. Abstract : Supplemental Digital Content is available in the text